Storable Good Monopoly: The Role of Commitment - Dudine, Paolo; Hendel, Igal; Lizzeri, Alessandro (American Economic Review, 2006)
We study dynamic monopoly pricing of storable goods in an environment where demand changes over time. The literature on durables has focused on incentives to delay purchases. Our analysis focuses on a different intertemporal demand incentive. The key force on the consumer side is advance purchases or stockpiling. In the case of storable goods, the stockpiling motive has recently been documented empirically. We show that, in this environment, if the monopolist cannot commit, then prices are higher in all periods, and social welfare is lower, than in the case in which the monopolist can commit. This is in contrast with the analysis in the literature on the Coase conjecture.